Some agricultural techniques to cope with the fluctuation of the groundwater level in arid environments: Case of the Souf Oasis (Algerian Sahara) - Bachir, Khezzani; Salah, Bouchemal; Youcef, Halis (Journal of Aridland Agriculture, 2016)
In arid lands, the unique characteristics of the date palm are the privilege of the main axis of oases ecosystems. In the Souf oasis, the palm trees are planted as form Ghout where these trees directly benefit from groundwater. The Ghout is a model for sustainable agricultural systems, saving water, soil and adapted to harsh conditions in arid lands. However, and because it is completely dependent on the groundwater level, it is considered precarious, by raising or lowering this slick threatens the palm trees, or by flooding or by drought. In this research paper, we showed two agricultural techniques that used by farmers to cope with the fluctuation of the water table, and in spite of its simplicity, they contributed for a long time to the preservation of the traditional irrigation system from disappearing.